Effect of gestational diabetes mellitus on the gut microbiota of male and female infants at 12 weeks: a hospital-based follow-up study - Cui ZHANG; Yongli ZHAO; Yifan DUAN; Yuanyuan ZHOU; Bei NIU; Changqing LIU (Zhongguo gonggong weisheng)
ObjectiveTo study the effects of gestational diabetes mellitus (GDM) on the gut microbiota of male and female infants. MethodsFrom June 2016 to December 2019, 913 singleton pregnant women (aged 18–45 years) attending prenatal examinations at a county hospital in Hebei province were enrolled in the study. Information on prenatal examinations and laboratory test results were collected, and their offspring were followed up to 12 weeks of age. Fresh fecal samples were collected from the infants as samples. Based on the results of two maternal fasting blood glucose tests (at 12 and 24 weeks of gestation), a total of 48 healthy full-term infants with no history of antibiotic use were divided into two groups: the GDM group, in which the mothers had fasting blood glucose levels ≥ 5.1 mmol/L on both tests, and the control group, in which the mothers had normal fasting blood glucose levels on both tests. 16S rDNA sequencing was performed using high-throughput sequencing technology. ResultsOf the 16 infants in the GDM group, 10 were male and 6 were female, while of the 32 infants in the control group, 17 were male and 15 were female. In the female infants, the Chao1 index of gut microbiota was lower in the GDM group than in the control group (t= –3.34, P< 0.01). LEfSe analysis showed that the highly expressed gut microbiota in the male infants of the GDM group were Lactobacillaceae and Lactobacillus, while in the female infants, it was Carnobacteriaceae. In male infants, the relative abundance of Lactobacillus was higher in the GDM group than in the control group (Z=4.66, P =0.03), and the relative abundance of Erysipelatoclostridium was lower in the GDM group than in the control group (Z= –4.45, P= 0.04). In female infants, the relative abundances of Lactobacillus and Rothia were lower in the GDM group than in the control group (Z= –10.19, P <0.01; Z= –4.42, P=0.04). There were no statistically significant gender differences in the gut microbiota at the phylum and genus level (all P > 0.05). ConclusionsCompared with the offspring of mothers with healthy pregnancies, the gut microbiota richness of female infants of mothers with GDM was reduced, which may also affect the relative abundance of Lactobacillus and Rothia in female infants. In addition, the gut microbiota richness of female infants was lower than that of male infants, but gender had no significant effect on the composition of the infant gut microbiota.